TEACHING METHODOLOGIES OF NATIVE LANGUAGE AND LITERATURE IN POLYTECHNICS - Khudoykulova Umida Alamjonovna (Bright Mind Publishing, 2025)
This article analyzes modern approaches to teaching methodologies of native language and literature in polytechnics, principles of competency-based education, as well as methods for improving the teacher's methodological skills. The article covers such issues as the integration of Sciences, the use of innovative pedagogical technologies, the formation of a culture of speech in students, the development of creative thinking on scientific and theoretical grounds. As a result, it was found that polytechnic students have the opportunity to develop interest in their native language and literature, broaden their thinking, and develop communicative competencies.
Keywords: Polytechnic, native language, literature, methodology, competence, educational technology, innovative approach, integrative education, student activism, interactive methods.